1997
DOI: 10.1080/02724936.1997.11747887
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity and growth performance of infants in Madura, Indonesia

Abstract: Between January 1987 and July 1988, all children born in two villages on the island of Madura, Indonesia were visited weekly by a field worker trained to interview mothers on disease symptoms. The maximum recall period was 1 week. All infants were measured (weight and height) at monthly intervals. Information on growth and morbidity is analysed for infants from birth until the age of 11 months. Morbidity, defined as acute respiratory tract infection (ARI), diarrhoea, fever and other diseases, is analysed over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
1
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 15 publications
2
7
1
2
Order By: Relevance
“…During this period, diarrhea was negatively associated with weight velocity but not with length velocity. This is consistent with results reported in some studies (Adair et al, 1993;Bittencourt et al, 1993;Rowland & Rowland, 1988), but differs from results of other studies in Honduras and Indonesia, where no relationship was demonstrated between diarrhea and growth of breast-fed infants in the ®rst 6 months (Cohen et al, 1995;Kolsteren et al, 1997). Differences in exposure to environmental pathogens may explain the inconsistencies in the various studies.…”
Section: Discussionsupporting
confidence: 47%
See 2 more Smart Citations
“…During this period, diarrhea was negatively associated with weight velocity but not with length velocity. This is consistent with results reported in some studies (Adair et al, 1993;Bittencourt et al, 1993;Rowland & Rowland, 1988), but differs from results of other studies in Honduras and Indonesia, where no relationship was demonstrated between diarrhea and growth of breast-fed infants in the ®rst 6 months (Cohen et al, 1995;Kolsteren et al, 1997). Differences in exposure to environmental pathogens may explain the inconsistencies in the various studies.…”
Section: Discussionsupporting
confidence: 47%
“…Prevalence of diarrhea and fever were negatively related to growth during the ®rst year of life. No signi®cant relationship could be demonstrated between respiratory illness and growth among these infants, even though this association has been reported by other investigators (Kolsteren et al, 1997;Ricci & Becker, 1996;Rowland & Rowland, 1988). Most studies, including ours, have not distinguished between upper vs lower respiratory illness.…”
Section: Discussioncontrasting
confidence: 40%
See 1 more Smart Citation
“…Furthermore, despite the close relationship between diarrhoea prevalence and growth faltering in this population reported in the 1970s (Rowland et al, 1977), a subsequent reduction in the incidence of diarrhoea was not associated with improved growth (Poskitt et al, 1999). Similar "ndings have been reported in other populations (Briend et al, 1989;Kolsteren et al, 1997).…”
Section: Introductionsupporting
confidence: 42%
“…Also there was no evidence of causal effects of breastfeeding on body mass index (BMI) and blood pressure in a study aimed to understand the confounding structure of breastfeeding by socio-economic position in the British Avon Longitudinal Study of Parents and Children or the Brazilian Pelotas 1993 cohorts study [18]. Several studies have shown negative associations between the number of infectious disease episodes during infancy mainly pneumonia, diarrhoea and physical growth of the child [19-22]. …”
Section: Introductionmentioning
confidence: 99%